Multifunctional photocatalytic materials for energy - Lin, Zhiqun, 1972-; Ye, Meidan; Wang, Mengye (Woodhead Publishing in materials., 2018)
Multifunctional Photocatalytic Materials for Energy discusses recent developments in multifunctional photocatalytic materials, such as semiconductors, quantum dots, carbon nanotubes and graphene, with an emphasis on their novel properties and synthesis strategies and discussions of their fundamental principles and applicational achievements in energy fields, for example, hydrogen generation from water splitting, CO2 reduction to hydrocarbon fuels, degradation of organic pollutions and solar cells. This book serves as a valuable reference book for researchers, but is also an instructive text for undergraduate and postgraduate students who want to learn about multifunctional photocatalytic materials to stimulate their interests in designing and creating advanced materials.